Examination of the Global Plant Factory's National Competitiveness via Artificial Intelligence-Driven Research Analysis - Wang, Feng; Park, Jae-Hoon (International Journal for Applied Information Management, 2023)
The plant factory is an advanced stage of the development of modern facility agriculture. It integrates biotechnology, engineering technology and system management to free agricultural production from the constraints of natural ecology and other objective conditions. A factory agricultural system that produces production according to human plans. Plant factories are one of the most dynamic and potential fields in the process of absorbing and applying high-tech achievements in the process of agricultural industrialization, and have attracted more and more attention from countries. This paper uses the SCI-EXPANDED database of Web of Science as the data source, adopts bibliometric methods, and focuses on the analysis of the competitiveness of various countries in the field of plant factory research in the world, providing information support and data reference for related.